An Investigation of YOLO-Based Helmet Detection for Workers on GPU and CPU Platforms - Viriyasatr, Kittakorn; Luangluewut, Warakorn; Thiennviboon, Phunsak; Charoensuk, Achitpon; Maleecharoen, Piyarose; Santironnarong, Siraphob; Thongsatapornwatana, Ubon; Kaewmongkol, Pantape (Defence Technology Academic Journal, 2025)
This research focused on enhancing workplace safety by detecting workers’ helmet usage through the integration of artificial intelligence with closed-circuit television systems (CCTV). The detection process was based on object detection techniques using the YOLO (You Only Look Once) model family. This study evaluates the performance of the latest versions—YOLOv10 and YOLOv11—on both CPU and GPU platforms, considering both detection accuracy and inference speed. Among the tested model variants, a maximum processing speed of 454.52 frames per second was achieved on GPU and 34.01 frames per second on CPU, demonstrating their suitability for real-time CCTV-based applications. In terms of accuracy, YOLOv11n achieved a mean Average Precision (mAP@50) of 98.3% for helmet detection and 96.6% for head detection. The model also demonstrated strong classification performance, with precision and recall of 85.76% and 96.98% for the head class, and 93.02% and 96.56% for the helmet class, respectively. These results confirmed the model’s effectiveness and balanced performance in distinguishing between helmeted and non-helmeted workers, supporting its potential for practical and cost-effective deployment in real-time safety monitoring systems.